2001
DOI: 10.1042/cs20010037
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of the carotid artery wall and baroreflex sensitivity after acute ethanol administration in young healthy volunteers

Abstract: The effects of ethanol administered orally (300 mg/kg in 250 ml of water) or intravenously (7.5 mg.min(-1).kg(-1) in 250 ml of saline over 40 min) on common carotid haemodynamics, wall mechanics and baroreflex sensitivity were compared with the effects of the intravenous infusion of 250 ml of saline. Ethanol or saline was administered to 10 healthy volunteers after 30 min of supine rest, and measurements were obtained 40 min (median; range 34-46 min) after administration. After ethanol administration, the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…The baroreflex did not improve significantly after beer drinking in contrast with the observation noticed after water consumption. Our findings are to some extent in agreement with previous reports showing reduced barorelex sensitivity after alcohol administration [11]. Explanation for the mechanism by which alcohol affects BRS range from direct interference with central regulation of the reflex to local carotid vasodilatation with decreased shear stress at receptor sites [12].…”
Section: Discussionsupporting
confidence: 93%
“…The baroreflex did not improve significantly after beer drinking in contrast with the observation noticed after water consumption. Our findings are to some extent in agreement with previous reports showing reduced barorelex sensitivity after alcohol administration [11]. Explanation for the mechanism by which alcohol affects BRS range from direct interference with central regulation of the reflex to local carotid vasodilatation with decreased shear stress at receptor sites [12].…”
Section: Discussionsupporting
confidence: 93%
“…However, we assessed fasting, postprandial and mean 24‐h triglyceride concentrations, and found that these were not significantly associated with any of the outcome variables in this study. Among healthy subjects, the association between triglyceride concentrations and arterial stiffness is also weak [15,34] or absent [35]. We conclude therefore that an increase in arterial stiffness is an unlikely explanation for the association between hypertriglyceridaemia and cardiovascular risk in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 97%
“…A BRS attenuation by continuous ethanol exposure or consumption has been shown in both experimental (29) and clinical (30) studies. Furthermore, acute ethanol administration has been described to decrease the BRS (31). However, it should be noted that all our patients had not been taking alcohol for at least 6 months.…”
Section: Discussionmentioning
confidence: 99%